2011
DOI: 10.1038/nrclinonc.2011.76
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs in body fluids—the mix of hormones and biomarkers

Abstract: Since the discovery of microRNAs (miRNAs), the study of these small noncoding RNAs has steadily increased and more than 10,000 papers have already been published. The great interest in miRNAs reflects their central role in gene-expression regulation and the implication of miRNA-specific aberrant expression in the pathogenesis of cancer, cardiac, immune-related and other diseases. Another avenue of current research is the study of circulating miRNAs in serum, plasma, and other body fluids—miRNAs may act not onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
1,092
1
12

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 1,321 publications
(1,110 citation statements)
references
References 122 publications
(145 reference statements)
5
1,092
1
12
Order By: Relevance
“…There is evidence implicating these derivatives of sncRNAs in cell‐to‐cell communication both in normal biology and in disease states (Cortez et al ., 2011; Hoy & Buck, 2012; Shah & Calin, 2012; Turchinovich et al ., 2012; Kosaka et al ., 2013). Our deep sequencing studies of serum/plasma have consistently detected tRNA‐derived RNAs of size 30–33 nt (Dhahbi et al ., 2013a,b).…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence implicating these derivatives of sncRNAs in cell‐to‐cell communication both in normal biology and in disease states (Cortez et al ., 2011; Hoy & Buck, 2012; Shah & Calin, 2012; Turchinovich et al ., 2012; Kosaka et al ., 2013). Our deep sequencing studies of serum/plasma have consistently detected tRNA‐derived RNAs of size 30–33 nt (Dhahbi et al ., 2013a,b).…”
Section: Introductionmentioning
confidence: 99%
“…In view of the possibility to use serum miRNAs as disease biomarkers, 31 we performed a miRNA microarray study using serum samples from vitiligo patients (n = 50) and healthy controls (n = 50). The assay identified 48 aberrantly expressed miRNAs (4twofold changes, Po0.01), among which 24 miRNAs (e.g., let-7b) were upregulated, whereas another 24 (e.g., miR-1914) were downregulated (Supplementary Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…Our method makes it possible to profile miRNA expression from tiny samples such as puncture biopsies. Recently, existence of miRNA in serum suggested that serum miRNAs may serve as potential convenient biomarkers for the detection and screen of various cancers and other diseases (19,20). The serum RNA yield is 1-2 lg/10 mL according a previous study (21).…”
Section: Discussionmentioning
confidence: 99%